Analisis Faktor yang Mempengaruhi Keputusan Pembelian Konsumen pada E-Commerce Shopee (Studi pada Mahasiswa Universitas Buana Perjuangan Karawang) - Absah Aenul Basor; Uus MD Fadli; Laras Ratu Khalida (BUDGETING : Journal of Business, Management and Accounting, 2023)
The purpose of this research is to explain the factors that influence consumer purchasing decisions in e-commerce. This study used a quantitative descriptive approach to the Shopee locus with a population of 311 students from the 2019 class of the Management Study Program, Faculty of Economics and Business, Buana Perjuangan University, Karawang. Samples were taken using the Slovin formula as many as 174 students. The data was obtained using a Likert-scale questionnaire distributed using the Google form. The data analysis method used Confirmatory Factor Analysis (CFA) using SPSS version 25. The results showed that there were 3 main factors, namely the advertising factor with a percentage value of 27.267%, the payment method factor with a percentage value of 13.478% and the ease of shopping factor with a percentage value of 12.166 %. Keywords : E-commerce, Factor Analysis, Purchase decision.